2017
DOI: 10.1038/s41598-017-14147-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anesthetic agents on overall and recurrence-free survival in patients undergoing esophageal cancer surgery: A retrospective observational study

Abstract: Given that surgical stress response and surgical excision may increase the likelihood of post-surgery cancer dissemination and metastasis, the appropriate choice of surgical anesthetics may be important for oncologic outcomes. We evaluated the association of anesthetics used for general anesthesia with overall survival and recurrence-free survival in patients who underwent esophageal cancer surgery. Adult patients (922) underwent elective esophageal cancer surgery were included. The patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 28 publications
5
142
3
Order By: Relevance
“…Given we did not examine the kinetics of neutrophil behaviors in various organs and blood, this needs to be clarified in the future. Resolution mediators LXA 4 and MaR1 levels were higher in the peritoneal fluid in sevoflurane group, suggesting that mice exposed to sevoflurane demonstrated earlier resolution from inflammation. LXA 4 facilitated peritoneal neutrophil phagocytic activity without apoptosis in CLP model (63), and MaR1 attenuated proinflammatory mediators and organ injury (64,65), which is in line with our survival result.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Given we did not examine the kinetics of neutrophil behaviors in various organs and blood, this needs to be clarified in the future. Resolution mediators LXA 4 and MaR1 levels were higher in the peritoneal fluid in sevoflurane group, suggesting that mice exposed to sevoflurane demonstrated earlier resolution from inflammation. LXA 4 facilitated peritoneal neutrophil phagocytic activity without apoptosis in CLP model (63), and MaR1 attenuated proinflammatory mediators and organ injury (64,65), which is in line with our survival result.…”
Section: Discussionmentioning
confidence: 87%
“…Because sevoflurane exposure was associated with better survival with less bacterial loads, we expected that inflammation might have started to resolve earlier in the sevoflurane arm. To test this hypothesis, we examined resolution mediators LXA 4 and MaR1 (46). The levels of both mediators were higher in the peritoneal fluid of sevoflurane-exposed mice (Fig.…”
Section: Sevoflurane Exposure Group Showed Earlier Resolution Of Inflmentioning
confidence: 99%
“…(25) Numerous studies have assessed the effects of anesthetics on mortality after various types of cancer surgeries. (26)(27)(28)(29). Although large randomized controlled trials are still required, a signi cant difference in the risk of mortality according to the anesthetic used in patients undergoing cancer surgery has been reported by previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Although large randomized controlled trials are still required, a signi cant difference in the risk of mortality according to the anesthetic used in patients undergoing cancer surgery has been reported by previous studies. (26)(27)(28) Against this background, it seems clear that, to optimize outcomes, the choice of anesthetic should be based on the characteristics of the individual case rather than the anesthesiologist's discretion. However, the literature on this topic is currently insu cient.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another retrospective study, of 922 patients undergoing oesophagectomy, reported that inhalational anaesthesia was associated with both worse overall survival (HR 1.58; 95% CI 1.24-2.01; P<0.001) and worse recurrence-free survival (HR 1.42; 95% CI 1.12-1.79; P¼0.003) after multivariable analysis adjustment. 9 However, despite biological plausibility and whilst the published work so far supports the notion that propofol-TIVA may confer a long-term survival benefit compared with inhalational anaesthesia, the evidence is low quality and we await the results of randomised controlled trials (RCTs).…”
Section: Matrix Codes 1a02 2a07 3j03mentioning
confidence: 99%